Sistem Kontrol Lampu Otomatis Pencegah Hama Berbasis Panel Surya dan Mikrokontroler - Tijaniyah; Alaika Nurir Roby; Muhammad Fikri Maula (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
Solar panels are devices that can convert solar energy into electrical energy. Photovoltaic technology (photovoltaic / PV) is used to convert solar radiation into electrical energy. Apart from being environmentally friendly, one of the main advantages of using solar panels as an energy source is that it can save on electricity bills. With solar panels can save electricity costs. plants that require intensive handling that requires them to stay for an unspecified period of time. The author is working on this scientific work with the aim of being able to design practical, economical, and efficient lighting in garden homes by using renewable energy or PLTS. Shallot farmers are now back using pest control to produce high-quality, spicy-tasting and pest-free shallots that make shallots rot. The right solution is to make an automatic pest control system for onion pests based on microcontrollers and solar panels that can save farmers' electricity. Solar panels are devices that convert sunlight energy into electrical energy. The solar panel functions to charge the control system device. Another advantage of this control system tool is that it can prevent onion pests with 2 25-watt LED lights for 7 hours at night